Pendampingan Kegiatan Membaca Siswa Kelas 1 MIS Miftahul Huda 2 Kota Palangka Raya Melalui Pengabdian Mahasiswa MBKM Asistensi Mengajar IAIN Palangka Raya - Diva Erviana; Muhammad Syabrina (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
The MBKM Teaching Assistance Program provides practical teaching experience for students in educational units where through the teaching assistance program, students gain real skills and experience in managing the learning process, interacting with students, as well as other teaching experiences. As a form of service at MIS Miftahul Huda 2 Palangka Raya City, researchers carried out one of the work programs, namely assisting reading activities in class 1. The aim of this reading assistance activity itself is to help students, especially class 1C, receive guidance in improving their reading skills. This program will be implemented for 4 (four) months starting from July-November 2024. Assistance with reading activities is going well and results in an improvement in the reading skills of grade 1 students.